2019
DOI: 10.1111/risa.13338
|View full text |Cite
|
Sign up to set email alerts
|

Illustration of a Method to Incorporate Preference Uncertainty in Benefit–Cost Analysis

Abstract: Benefit–cost analysis is widely used to evaluate alternative courses of action that are designed to achieve policy objectives. Although many analyses take uncertainty into account, they typically only consider uncertainty about cost estimates and physical states of the world, whereas uncertainty about individual preferences, thus the benefit of policy intervention, is ignored. Here, we propose a strategy to integrate individual uncertainty about preferences into benefit–cost analysis using societal preference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In this study, we focused on several key variables to define the outage scenario (outages fixed at 10-day duration, back-up coverage at 20 A and weather conditions below freezing). These estimates could be used in regional investment decision-making problems under these specified conditions (Baik et al 3,34 are examples), but should not be generalized to investment decisionmaking that involves significantly different conditions. However, using the methods developed in this study, it is possible to construct context-specific customer-damage functions by conducting a series of studies across different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on several key variables to define the outage scenario (outages fixed at 10-day duration, back-up coverage at 20 A and weather conditions below freezing). These estimates could be used in regional investment decision-making problems under these specified conditions (Baik et al 3,34 are examples), but should not be generalized to investment decisionmaking that involves significantly different conditions. However, using the methods developed in this study, it is possible to construct context-specific customer-damage functions by conducting a series of studies across different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The need to develop personalized uncertainty ranges for gauging the acceptability of a hypothetical regulation evolved into an alternative stated-preferences method (Finkel & Johnson, 2018), involving a multiple-bounded discrete choice preference elicitation method (cf. Baik et al, 2019). Table 1, derived from our earlier studies (Finkel & 1 Only about 35% of 95 micro-risk stated preferences studies conducted between 1973 and 2009 reported using trims; if and how many studies trimmed but did not report those trims is unknown (Braathen et al, 2011) Johnson & Finkel, 2016) and our subsequent macro-risk research experience, compares several attributes of the conventional and the novel macro-risk stated preference approaches.…”
Section: Eliciting Lay National Tradeoffsmentioning
confidence: 99%
“…The need to develop personalized uncertainty ranges for gauging the acceptability of a hypothetical regulation evolved into an alternative stated‐preferences method (Finkel & Johnson, 2018), involving a multiple‐bounded discrete choice preference elicitation method (cf. Baik et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CBA is widely used to evaluate alternative courses of action that are designed to achieve appropriate policy objectives [26]. When travel time reduces, passengers experience lower travel time; all should be accounted for benefit analysis.…”
Section: Primary Analysis Of Cost and Benefit Elementsmentioning
confidence: 99%